How do we educate future innovation managers? Insights on innovation education in MBA syllabi. Issue 1 (2nd January 2016) - Kars-Unluoglu, Selen
Abstract : Innovation education is regarded as a critical area in most business schools. This growing importance is partly a strategic response to managing in a knowledge-driven competitive environment. Given the expansion in popularity of innovation courses, it is surprising that little is known about the content and process of innovation education. This paper reports on the results of an exploratory study aiming to establish what is taught and how it is taught in innovation courses. This involves analysis of course syllabi of 29 innovation courses at 20 top-ranked business schools. Results revealed that although there is a consensus on the process of innovation education, shying away from traditional didactic approaches toward a more explorative and experiential mode, there exists substantial variation in course content. While this is not indicative of the quality of individual courses, it suggests that members of the innovation community run very dissimilar courses in their teaching practices. A common motif was found around multidisciplinarity and balanced coverage of static and dynamic components of innovation. Implications of findings for innovation teaching, pedagogy and curriculum development are discussed and benchmarks developed for evaluating existing curricula by instructors.